Isomer‐Dependent Photovoltaic Properties of the [6, 6]‐Phenyl‐C61 (or C71)‐Butyric Acid Methyl Esters. Issue 7 (16th April 2021) - Deng, Lin-Long; Zhan, Xin-Xing; Lin, Jheng-Wei; Ho, Rong-Ming; Zheng, Lan-Sun; Xie, Su-Yuan
Abstract : Isomerism is common in fullerene derivatives, and the isomer‐dependent photovoltaic performance of fullerene derivatives is envisaged recently. This review article outlines recent progresses on isomerism of [6, 6]‐phenyl‐C61 (or C71 )‐butyric acid methyl esters (PCBMs), one of the most prevalent electronic acceptors in organic or perovskite solar cells. Recent developments about the effects of PCBMs isomers on the photovoltaic performance and device stability of organic or perovskite solar cells are summarized, including the mono‐ and bis‐adduct of PC71 BM as well as the bis‐adduct of PC61 BM. The open questions and future directions with involvement of isomeric PCBMs are also discussed. Abstract : Recent developments about the isomer effects of [6, 6]‐phenyl‐C61 (or C71 )‐butyric acid methyl esters (PCBMs) on the photovoltaic performance and device stability of organic or perovskite solar cells, including the mono‐ and bis‐adduct of PC71 BM as well as the bis‐adduct of PC61 BM, are reviewed. The isomer‐dependent photovoltaic performances of fullerene‐based solar cells are susceptible to the isomeric structure and formulation involved.